Public policy and governance in Nigeria: The challenges of policy agenda setting - Ugo Okolie; Joel Dimiyen Bisina (Qualitative Research of Business and Social Sciences, 2026)
Policy agenda setting is a crucial component of the policy-making process, as it determines which public issues are brought to the forefront of government attention and how they are prioritized. In a nation as ethnically diverse and politically intricate as Nigeria, this stage is frequently influenced by competing regional interests, fragile institutional structures, and fluctuating political commitment. This study explores the relationship between public policy agenda setting and ethnoreligious consciousness in Nigeria. Using the Multiple Streams Framework as its analytical lens, the study demonstrates how political, social, and institutional forces impede the development of a unified national agenda, resulting in disjointed policies and slow responses to societal challenges. Employing a qualitative research design, the study analyzed collected data using thematic content analysis. The findings reveal that the interplay of power, perception, influence, and proximity in political mobilization and policy development significantly affects how ethnicity and religion intersect, frequently reducing broader historical and geopolitical issues to ethnic confrontation. The study concludes that the intentional use of ethnic consciousness by political actors, who invoke shared group identities during national debates, lies at the core of many instances of ineffective policymaking in present-day Nigeria. It further underscores the need for stronger institutions, inclusive governance practices, and improved civic participation to ensure that policy agendas reflect the broader national interest